The Routledge international handbook of community psychology facing global crises with hope - Kagan, Carolyn; Akhurst, Jacqueline; Alfaro, Jaime; Lawthom, Rebecca; Richards, Michael; Zambrano, Alba (Routledge international handbooks, 2022)
"This handbook offers a unique critical, and cross-disciplinary approach to the study of community psychology, showing how it can address the systemic challenges arising from multiple crises facing people across the world. Addressing some of the most pressing issues of our times, the text shows how community psychology can contribute to principled social change, giving voice, enabling civic participation, and supporting the realignment of social and economic power within planetary boundaries. Featuring a collaboration of contributions from world-leading academics, early career researchers and community leaders, each chapter gives theory and context with practical examples of working with those living in precarious situations, on matters that concern them most, and highlights positive ways to contribute to progressive change. The editors examine economic, ecological, demographic, gender, violence, energy, social and cultural, and political crises in relation to psychological theories, as well as public policy and lived experiences, presenting an approach situated at the intersection of public policy and lived experiences. Viewed through four different perspectives or lenses: a critical lens; a praxis lens; an ecological lens; and a reflective lens, this compendium of critical explorations into community psychology shows how it can contribute to a fairer, more just, resilient, and sustainable world. Also examining the lessons learnt from the COVID-19 pandemic about the pervading nature of social inequality, but also the potential of solidarity movements ranging from local to international levels, this is ideal reading for undergraduate and postgraduate students and scholars in community psychology and related areas, including social psychology, clinical psychology, and applied psychology"--